The tutorial function in the educative ambit (Journal of Parents and Teachers, 2012)
Lectures are individual classes between teachers and students for them to better understand the material of classes in case of doubts. The author explains the main focus of the lectures and why is important to continue applying them.
Keywords: Lectures; education; learning process.